THE RELATIONSHIP BETWEEN SELF-ESTEEM AND PUBLIC SPEAKING ANXIETY AMONG STUDENTS OF RAJEKWESI HEALTH COLLEGE, BOJONEGORO - M. Nashihul Hikam; Evita Muslima Isnanda Putri; Agus Ari Afandi; Rahmawati (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Public speaking anxiety is a common psychological problem experienced by students and can be influenced by an individual's level of self-esteem. This study aims to analyze the relationship between self-esteem and public speaking anxiety among students at Rajekwesi Health College, Bojonegoro. The study used a quantitative approach with a correlational design and cross-sectional method. The study population was 461 students with a sample of 70 respondents selected using quota sampling techniques. The research instruments used were the Rosenberg Self-Esteem Scale (RSES) and the Hamilton Anxiety Rating Scale (HARS). Data analysis was performed using the Spearman Rho test with a significance level of 5%. The results showed that students with high self-esteem tended to have lower levels of public speaking anxiety. Statistical tests showed a significant relationship between self-esteem and public speaking anxiety in students. The conclusion of this study is that self-esteem plays an important role in influencing the level of public speaking anxiety, so that increasing self-esteem can help improve students' communication skills.